The Characterization of Hua Mulan in Disney’s 2020 Live-Action Mulan - Ni Komang Arie Suwastini; Made Ayu Wiranti; I Ketut Supir; Ida Ayu Made Istri Utami (Indonesian Journal of Religion and Society, 2022)
Disney's 2020 live-action film Mulan is remade of the 1998’s cartoon version, with several changes, including the characterization of the main character. This study aims to investigate the characterization of Hua Mulan as the main female character in Disney's 2020 Live-Action Mulan. Using the qualitative interpretive method by Miles, Huberman, & Saldana (2014), the research was conducted in four simultaneous processes: data collection and condensation, data display, and conclusion drawing/verification. This research revealed that Mulan is a village girl who was reckless, brave, strong, and often acted like a boy. When Mulan grew up, she became a brave and tough person who made she could protect herself and her family. Moreover, it reflects Mulan's independence which is represented by her ability to survive and fight alone for the sake of her family and empire. Furthermore, Mulan also had an extraordinary "Chi" power that made her a strong warrior. Her family and society also respected Mulan for her honesty in revealing her mistakes. The depiction of Mulan, who has a masculine character, implies that Disney's 2020 live-action Mulan can be used as a role model by the audience in protecting and loving those around them.